2021
DOI: 10.3390/ijerph18199947
|View full text |Cite
|
Sign up to set email alerts
|

How Do Environmental Concerns and Governance Performance Affect Public Environmental Participation: A Case Study of Waste Sorting in Urban China

Abstract: Environmental pollution threatens public health and has become a social concern in recent years. Despite the conditions for public participation in environmental governance have improved considerably, the level of public engagement in government projects still falls short of expectations. Therefore, this article introduced two key variables, hoping to answer the following research question that how environmental concerns and governance performance affect public environmental participation. Through principal co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 52 publications
(55 reference statements)
0
10
0
Order By: Relevance
“…The selection of control variables in this paper is similar to that of Yang et al [70]. Yin et al demonstrated that public environmental concerns have no significant impact on their environmental engagement [60], considering gender, age, and income levels as control variables. Also, Chen et al studied the relationship between environmental information and public participation, gender, age, education level and income included in the control variables, and they were hardly noticeable [50].…”
Section: Benchmark Regressionmentioning
confidence: 86%
See 2 more Smart Citations
“…The selection of control variables in this paper is similar to that of Yang et al [70]. Yin et al demonstrated that public environmental concerns have no significant impact on their environmental engagement [60], considering gender, age, and income levels as control variables. Also, Chen et al studied the relationship between environmental information and public participation, gender, age, education level and income included in the control variables, and they were hardly noticeable [50].…”
Section: Benchmark Regressionmentioning
confidence: 86%
“…In addition, environmental concerns have been shown to mediate the relationship between waste sorting and green consumption behavior [22,38,47,59]. On the other hand, public environmental concerns have been proven to have no significant impact on people's environmental participation [60]. There are still questions about the impact of PEC on PEB.…”
Section: Pec and Pebmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, public participation is an integral part of a modern environmental governance system. Public participation is also closely related to government environmental information disclosure [19]. The government takes environmental information disclosure as its leading role and has established a widely supervised public opinion network.…”
Section: Environmental Information Disclosurementioning
confidence: 99%
“…Modern environmental governance needs to involve the public in the environmental governance system, which can play the role of pressure transmission and supervision and urge the implementation of environmental protection policies [ 17 ]. Yin et al, found that by mobilizing the public to participate in environmental governance through education, publicity, mobilization, and incentives, etc., the government can effectively improve the public’s awareness of environmental protection and improve the performance of environmental governance [ 18 ]. Wu believes that the quality and satisfaction of environmental governance can be effectively improved by incorporating the public into the environmental governance system as a party of diversified governance and giving play to the subjective initiative of the public [ 19 ].…”
Section: Introductionmentioning
confidence: 99%